Recruiting patients to a digital self-management study whilst in hospital for a chronic obstructive pulmonary disease exacerbation: a feasibility analysis - Whelan, M; Biggs, C; Areia, C; King, E; Lawson, B; Newhouse, N; Ding, X; Velardo, C; Bafadhel, M; Tarassenko, L; Watkinson, P; Clifton, D; et al. (SAGE Publications, 2021)
Background Patients with chronic obstructive pulmonary disease (COPD) are often hospitalised with acute exacerbations (AECOPD) and many patients get readmitted. Intervening with hospitalised patients may be optimal timing to provide support. Our previous work demonstrated use of a digital monitoring and self-management support tool in the community. However, we wanted to explore the feasibility of recruiting patients whilst hospitalised for an AECOPD, and to identify the rate of dropout attrition around admission for AECOPD.